Influence of Learning Management Systems on Teaching and Learning in Saudi Universities - Alenezi, Abdullah (Advances in Social Sciences Research Journal, 2018)
This paper investigated the impacts of Learning Management Systems (LMSs) on education in Saudi Universities, to ascertain the effectiveness of LMSs in this setting, and the challenges met during their implementation. Both qualitative and quantitative approaches were used to investigate the influence of LMS on teaching and learning in three universities in Saudi Arabia. The study adopted both questionnaires and interviews to collect data from 100 students and 101 lecturers in relation to their attitudes to LMS use at their respective institutions. The 201 participants were sampled from the three universities using a stratified random sampling method, where an almost equal proportion of students and teachers from the institutions were involved in the study. The results showed that proper use of LMS reduces time wastage among students and allows them to handle their professional and academic lives simultaneously. Meanwhile, lecturers receive training and learn how to operate the LMS systems for academic purposes, but at times find this a time-consuming process that requires more administration than teaching input. The outcome of this study is significant in expounding the positive as well as negative impacts of LMSs on education in higher learning. More so, it brings into the fore the need for university administrations to consider adopting such a system as a contemporary approach in learning and teaching in the universities to enhance the learning process. The results may also form a basis upon which policymakers in the educational sector may formulate sound policies to enhance and promote quality education in Saudi Arabian universities.